Cannabis use, COMT, BDNF and age at first-episode psychosis. (April 2017) - Mané, Anna; Bergé, Daniel; Penzol, Maria Jose; Parellada, Mara; Bioque, Miquel; Lobo, Antonio; González-Pinto, Ana; Corripio, Iluminada; Cabrera, Bibiana; Sánchez-Torres, Ana Maria; Saiz-Ruiz, Jerónimo; Bernardo, Miguel; et al.
Abstract: Although an interaction between COMT Val158Met and BDNF Val66Met polymorphisms with cannabis use has been proposed with respect to the risk of psychosis emergence, findings remain inconclusive. The aim of the present study was to evaluate the different possible associations between these polymorphisms and early cannabis use and the age at the first episode of psychosis. The relationship between age at psychosis onset and COMT Val158Met and BDNF Val66Met polymorphisms with early cannabis use as well as those factors associated with early cannabis use were investigated. Among 260 Caucasian first-episode psychosis patients, early cannabis use and the presence of the met-allele from the BDNF Val66Met polymorphism were significantly associated with age at psychosis onset. Furthermore, early cannabis use was significantly associated with male gender in the logistic regression analysis. These findings provide evidence of the important role of early cannabis use and the Val66Met BDNF polymorphism on age at psychosis onset and they point out to sex-specific differences in cannabis use patterns.